Loneliness, social dislocation and invisibility experienced by older men who are single or living alone: accounting for differences across sexual identity and social context. Issue 2 (27th February 2022) - Willis, Paul; Vickery, Alex; Jessiman, Tricia
Abstract: Across literature on loneliness and ageing, little attention is given to the intersection of ageing, sexuality and masculinities, and how this shapes the social connections of older men. We report findings from a qualitative study of older men's experiences of loneliness and social participation, focusing on perspectives from two groups who are single and/or living alone: men identifying as (a) heterosexual and (b) gay (not bisexual). We present findings generated from semi-structured interviews with 72 men residing in England (65–95 years). We discuss three prominent themes: (a) loneliness, loss and social dislocation; (b) diverging life-events that trigger loneliness; and (c) variations in visibility and exclusion across social settings. Embedded within men's descriptions of loneliness is a running theme of social dislocation that speaks to a wider sense of social separation and estrangement. Unique to gay men's accounts are the ways in which experiences of loneliness and social isolation are compounded by living in heteronormative social environments and their encounters with ageism in gay social settings. Older men's accounts convey anxieties about visibility and anticipated exclusion across social settings shared with other men that vary according to sexual identity and context. We discuss how sexuality and being single and/or living alone impact on older men's social participation as we seek to move beyond a heterocentric understanding of loneliness.